The Effect Of Traumatic Life Events On Traffic Rules: Evaluation in the Context of Driving with Under Effect of Alcohol - Yeşil, Aslı; Demircan, Yusuf Tunç; Aker, Ahmet Tamer (The Bulletin of Legal Medicine, 2020)
Objective: The aim of this study is to determine the frequency of traumatic experiences of drivers who are driving with alcohol and to determine traffic punishment information. In addition to investigate the relationship between traumatic history and criminal information. Materials and Methods: The study was conducted with 295 participants who participant in Driver Behaviour Development Training Programme conducted by Bursa Health Directorate between November 2015 and June 2016. Driver Information Form which was include demographic and traumatic life event information were used to obtain the data. In addition, driver’s license criminal information was requested from the Police Department with official letter. Results: The mean age of the drivers was 40.47±9.48. Of the cases, 11.2% (n:33) had a life-threatening illness or injury, 10.8% (n:32) had having a serious accident or injured, 9.5 % (n:28) having had threated physical violance or weapons. Of the cases, 21.4 % (n: 63) who was lost by accident, murder or suicide one of the family member (lover, spouse, or very close friend), 6.1% (n:18) stated that had been threatened with death or serious injury. It was found that drivers most frequently contravened article 34 with 46.9 % and then contravened article 45.8 % with 51/2-A, 38.2 % eith 78/1-A, and 30.2% with 118/7. Conclusion: In this study conducted with drivers who had a history of driving under effect of alcohol, significant relationship was found between lifelong traumatic history and traffic controventions. Keywords: Forensic Sciences; Traumatic Life Events; Crime